From Edmund Husserl to Wolfgang Iser: Phenomenological Reduction and Literary Text - Periša, Josip (Poznańskie Studia Slawistyczne, 2025)
The aim of this paper is to analyze a representative text of Wolfgang Iser’s phenomenological approach to literary texts in relation to its philosophical legitimacy, the phenomenology of Edmund Husserl, considering his method of phenomenological reduciton. The paper will present how Wolfgang Iser understands the engagement with literary texts in accordance with the fundamental principles of phenomenology, with an emphasis on setting aside one’s own experience in order to adequately engage with the literary text. Then, it is of crucial importance to connect this seemingly simple postulate with the philosophical legitimacy from which it arises, which is precisely the method of phenomenological reduction that the father of phenomenology, Edmund Husserl, most radically developed in his Ideas from 1913.